Kajian Proses Pelaksanaan dan Perhitungan TKDN - Roselina Rahmawati (President University, 2016)
This study is about the study of the implementation process and calculation of TKDN (Domestic Component Level). Industrial work in Indonesia are expected to use the main ingredients sourced from Indonesian local products. So that the service provider / goods must have Domestic Component Level (TKDN)> 25% (more or equal to 25%), price preference in TKDN can only be given to goods with TKDN content> 25%. This study was conducted with a study literature from indonesian regulation. So from the results of the study obtained the implementation phase and calculation formula TKDN that can be used to determine the percentage of the level of use of local products used.